2012
DOI: 10.1002/hbm.22112
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment is associated with an automatic negative emotion processing bias in the amygdala

Abstract: the present association of limbic bias and maltreatment was demonstrated in the absence of psychopathological abnormalities, thereby limiting strong conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
163
3
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(197 citation statements)
references
References 83 publications
(105 reference statements)
12
163
3
11
Order By: Relevance
“…This linear association remained significant after controlling for individual differences in age, IQ, experimental sequence, GMV of corresponding areas, neuroticism, self-esteem, and trait anxiety. ELS has previously been associated with limbic hyper-responsiveness to negative facial cues during early stage of emotion processing (Dannlowski et al, 2013). Impaired structural connectivity within the limbic-prefrontal circuit has also been observed in subjects who have experienced ELS (Hart and Rubia, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…This linear association remained significant after controlling for individual differences in age, IQ, experimental sequence, GMV of corresponding areas, neuroticism, self-esteem, and trait anxiety. ELS has previously been associated with limbic hyper-responsiveness to negative facial cues during early stage of emotion processing (Dannlowski et al, 2013). Impaired structural connectivity within the limbic-prefrontal circuit has also been observed in subjects who have experienced ELS (Hart and Rubia, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…relation to childhood trauma (Dannlowski et al, 2012;van Harmelen et al, 2013), these studies did not take the relationship between emotional valence and skills subserving emotion regulation into account. An interesting study by Tottenham et al (2011) that examined the influence of amygdala activity for fearful compared to neutral faces during inhibitory control in previously institutionalized children did unfortunately not examine happy faces.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that childhood maltreatment was associated with increased neural responses in the amygdala to presentation of both angry and happy emotional expressions in one study 3 and to presentations of only sad facial expressions in another study. 4 In combination with genetic factors, such childhood maltreatment-induced alterations might set the stage for the development of psychopathology. In support of this suggestion, we demonstrated previously that childhood adversity interacts with genetics and affects hippocampal volumes in patients with major depressive disorder (MDD).…”
Section: Introductionmentioning
confidence: 99%